Empowering females through beauty for better life program as corporate social responsibility - Rodiah, Saleha; Dida, Susanne; Maryani, Eni; Mustaffa, Normah (PRofesi Humas, 2024)
Background: Low-economic Female Heads of Household (FHH) needs to be empowered amidst a patriarchal culture. The Female Heads of Household Empowerment Foundation (PEKKA) has developed a partnership with L’Oreal to empower FHH through hairdressing training, called Beauty for a Better Life (BFBL). Purpose: This study investigated the FHH empowerment program as a corporate social responsibility in Cianjur through the framework of partnership, support, and impact. Methods: This case study adopted a qualitative approach with seven informants. It examined FHH empowerment activities under the L’Oreal CSR program in Cianjur. Data was obtained through interviews, observations, and literature studies. Analysis techniques consisted of data collection, data reduction and presentation, and conclusion drawing. Results: Partnerships are established to open FHH access to resources and build economic independence. Support for the CSR implementation includes competent coaches, funds, curricula, products, and advocacies. The program successfully empowers the community economically, increases self-confidence, and builds motivation for self-capacity. Conclusion: The partnership overcomes the obstacles of FHHs to engage in the CSR program. L’Oreal has supported the FHH with the CSR program towards a sustainable and advanced community. The training results have a positive impact and support for empowered FHH. Implications: This study suggested enhancement of FHH access to education, employment, or other resources. Besides, strengthening self and family capacity has a significant long-term impact on improving economic and social independence. Furthermore, inter-sector collaboration is vital to support the FHH empowerment and to deliver recommended policies to improve the effectiveness of relevant programs in the future.